Addressing Burnout Through Spiritual Mentorship: Enhancing Motivation and Well-Being of Islamic Education Teachers - Laura Paramita; Fathul Jannah; Lina Revilla Malik (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of spiritual mentoring as an effort to address burnout among Islamic Education teachers, with specific attention to its forms, mechanisms, and impact on teachers’ psychological well-being. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation involving Islamic Education teachers, school leaders, and relevant stakeholders. The data were analyzed using thematic analysis to identify recurring patterns related to spiritual mentoring practices and teacher burnout. The findings reveal that spiritual mentoring was implemented through structured and routine activities, including collective dhikr, Qur’anic recitation, morning spiritual gatherings, and ruhiyah mentoring integrated into the school culture. These practices contributed to reducing emotional exhaustion, fostering inner calm, strengthening professional motivation, and helping teachers rediscover deeper meaning in their educational roles. The success of the program was supported by spiritually oriented leadership, a supportive organizational culture, and institutional commitment to teacher well-being. Theoretically, this study reinforces the relevance of tazkiyatun nafs within Islamic psychotherapy as a holistic framework for addressing burnout, while also expanding the discourse on the integration of spirituality and educational psychology. Practically, the findings imply that Islamic educational institutions should systematically incorporate spiritual mentoring into human resource management to enhance teachers’ well-being, resilience, and professionalism.